Deafness in Australian Cattle Dogs associated to QTL on chromosome 20 in genome‐wide association study analyses - Seddon, J. M.; Fortes, M.; Kelly‐Smith, M.; Sommerlad, S. F.; Hayward, J. J.; Burmeister, L.; De Risio, L.; Mellersh, C.; Freeman, J.; Strain, G. M. (Animal genetics, 2021)
Summary Pigment‐associated deafness is a common hereditary condition in a range of dog breeds. The aim of this study was to perform a genome‐wide association analysis to investigate the genetic architecture of deafness in Australian Cattle Dogs. Genotypes for 104 757 polymorphisms in 216 dogs were available for analyses after quality control. A genomic relationship matrix was used in the mixed model analyses to account for polygenic effects, as we tested each polymorphism for its association with deafness, in a case/control experimental design. Three approaches were used to code the genotypes and test for additive, recessive and dominant SNP effects. The genome‐wide association study analyses identified a clear association peak on CFA20, with the most significant SNPs on this chromosome (1.29 × 10−4) in the vicinity of MITF. Variants in MITF have been associated with white pigmentation in dogs and with deafness in humans and other species, supporting the premise that canine deafness is associated with variants in or near this gene. A recessive inheritance for the peak in CFA20 is possible given the significant results in the recessive model; however, the estimated heritability was low (4.54 × 10−5). Further validation, identification of variants and testing in other dog breeds are needed.